Single phase pulse width modulation rectifier / Mohamad Sahar Tahir - Tahir, Mohamad Sahar (2011)
After the development of semiconductors, conversion from AC source to DC source is possible. Earlier, conventional diode rectifier does not offer the control ability of its operation. Later, advanced development of semiconductors has made the rectifier with control ability. Phase controlled thyristor rectifier became very popular but it was found that they also created negative side effects which injected current harmonics to the supply network which affected power quality. Nowadays, modern industrial demanded control features of power converters while new regulations impose more stringent limits to current harmonics injected by the power converters. The introduction of single phase PWM rectifier is present in this thesis, its operation, switching technique and control technique was studied. The design of all variable parameters in the converter is also present. The results of simulation by using Matlab Simulink software and the calculation design are compared.